O dever de cooperação dos sujeitos processuais no direito processual civil brasileiro: uma meta-análise dos estudos produzidos pela literatura processual brasileira. - Lima, Ana Catharine Rodrigues Pereira (2017)
This is the present research of a meta-analysis about the duty of procedural cooperation exercised from three specialized periodicals in Procedural Law. Leaning over the scientific articles of the Journal of Process, the Dialectic Processes Journal and the Brazilian Journal of Procedural Law, this study try to find answer the question that inaugurated it: how the Brazilian civil procedural literature dealt with the duty of procedural cooperation, in the period between 1989 and 2017? In force of the Federal Constitution of 1988 defined the choice of the initial frame of this research. Under the hypothesis that there would be a uniformity of treatment in the published studies on procedural cooperation in the Brazilian civil procedural literature, as well as the possibility of these studies having developed as a consequence of the legal provision that started to provide for procedural cooperation in form expressed in the CPC of 2015, it was sought to identify, in the literature accessed when and in what way the topic of procedural cooperation was treated, as well as the number of times it was approached, as well as the immediate criteria for analyzing the data collected. Therefore, the research evolution stages were carried out according to the phases that the meta-analysis requires to be effectively carried out. The dogmatic chapters developed aim only to access the foundations necessary to the knowledge and identification of the proposed research problem. Some distinctions and similarities were observed in the way the studies published in the periodicals dealt with the researched subject, among other situations. We then defined categories of analysis in relation to the data collection, and, once applied in the interpretative graphs of these data, we pointed out the results of the research. This paper does not aim to position itself on the subject researched, but only presents an overview that can serve to guide and adapt future studies, considering that it can diagnose if there are excesses or gaps, superficiality or deepening, among other factors, in the studies published by the analyzed journals. It may also contribute to the development of future academic research on the same theme, insofar as the results found by this research can be accessed, for example, before a literature review, pointing out, from the results found here, which journals should be accessed, considering how the topic was treated. For these reasons, the work presented here may become an instrument of consultation for future studies on procedural cooperation, which may have the expense of research time possibly minimized.